Trends in Irish hip fracture surgery over a 7-year period and international registry comparison. Issue 2 (April 2022) - Irwin, Shane C.; Hughes, Andrew J.; Sheehan, Eoin; Merghani, Khalid
Abstract: Background: Hip fractures are a significant cause of morbidity and mortality in elderly patients. Timely surgical fixation and early mobilisation are the cornerstone to successful outcomes. The Irish Hip Fracture Database (IHFD) was established in 2012 and publishes annual reports on hip fracture care. This paper describes the trends in surgical fixation in Ireland during a 7-year period (2013–2019), assesses for compliance with guidelines and compares the most recent published reports from ten international hip fracture registries. Methods: All published IHFD reports were systematically reviewed and tabulated. Data corresponding to demographics, fracture type, surgical fixation and post-operative management was plotted and analysed. Ten international hip fracture registries were identified and reviewed. Data was extracted corresponding to the IHFD dataset. Results: A total of 21, 684 hip fractures were recorded during this period. The majority of patients were female (70.16%), >80 years old (58.26%), admitted from their own home (82.13%) and ASA grade 3 (53%). The majority of undisplaced and displaced intracapsular fractures were treated with hemiarthroplasty, 62% and 88% respectively. There has been a decline in the use of dynamic hip screw (DHS) for intertrochanteric fractures with intramedullary nails being favoured. Conclusion: Despite greater awareness of hip fracture care through the IHFD and the introduction of Best Practice Tariffs (BPT), further improvements are needed. Ireland compares well to international standards but has low rates of compliance to NICE guidelines for surgical fixation. Highlights: Ireland compared well to international hip fracture registries. Decline in use of DHS for intertrochanteric fractures. IM nails increasingly favoured for intertrochanteric and subtrochanteric fractures. Irish THR rates remained low at 7% for intracapsular fractures. Further improvements required to meet Best Practice Standards.